Effect of Chelerythrine on Intestinal Cell Turnover following Intestinal Ischemia-Reperfusion Injury in a Rat Model - Sukhotnik, Igor; Bitterman, Sivan; Shahar, Yoav Ben; Pollak, Yulia; Bitterman, Nir; Halabi, Salim; Coran, Arnold G.; Bitterman, Arie (European Journal of Pediatric Surgery, 2017)
Background Chelerythrine (CHE) is a benzophenanthridine alkaloid that is a potent, selective, and cell-permeable protein kinase C inhibitor. The purpose of the present study was to examine the effect of CHE on intestinal recovery and enterocyte turnover after intestinal ischemia-reperfusion (IR) injury in rats.Methods Male Sprague-Dawley rats were divided into four experimental groups: (1) sham rats underwent laparotomy, (2) sham-CHE rats underwent laparotomy and were treated with intraperitoneal CHE; (3) IR-rats underwent occlusion of both superior mesenteric artery and portal vein for 30 minutes followed by 48 hours of reperfusion, and (4) IR-CHE rats underwent IR and were treated with intraperitoneal CHE immediately before abdominal closure. Intestinal structural changes, Park injury score, enterocyte proliferation, and enterocyte apoptosis were determined 24 hours following IR. The expression of Bax, Bcl-2, p-ERK, and caspase-3 in the intestinal mucosa was determined using real Western blot and immunohistochemistry.Results Treatment with CHE resulted in a significant decrease in Park injury score in jejunum (threefold decrease) and ileum (twofold decrease), and parallel increase in mucosal weight in jejunum and ileum, villus height in jejunum and ileum, and crypt depth in ileum compared with IR animals. IR-CHE rats also experienced a significantly lower apoptotic index in jejunum and ileum, which was accompanied by a lower Bax/Bcl2 ratio compared with IR animals.Conclusions Treatment with CHE inhibits programmed cell death and prevents intestinal mucosal damage following intestinal IR in a rat.
Keywords: ischemia-reperfusion; intestine; chelerythrine; apoptosis